Komodifikasi Upacara Religi Dalam Pemasaran Pariwisata - Dhyah Ayu Retno Widyastuti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2011)
Development of tourism program is basically done as an effort to support income sources. Policy of tourism is a key factor in its. Facts showed that the policy has not been fully align ed to the local societies. Commodification of religious ceremony is a form of marketing process undertaken to attract tourists. Critical theory approach is used which the implications can be explored through the political economy perspective in the case studies. The results showed that policies of tourism lead to economic political activities in the form of commodification of religious ceremony. Hindu’s communities as an “object” of tourism policy implementation.